Portfolio Reasons for Homeownership: The Case of Immigrants (2020)
This paper uses data from the Legalized Population Survey to study the determinants of U.S. immigrant’s home ownership. The main interest of the paper is on the relationship between house ownership in the U.S. and house ownership abroad. The results show that house ownership of U.S. immigrants is positively related to house ownership abroad. The results are especially significant for females and for the ownership of a second house in the U.S. These results seem to imply that migrants balance their portfolios between housing investments in the U.S. (safe assets) and housing investments abroad (risky assets). It is possible that these housing investments abroad can account for some of the low house ownership rates that previous studies have found for U.S. immigrants